2017
DOI: 10.5664/jcsm.6494
|View full text |Cite
|
Sign up to set email alerts
|

Listening to the Patient Voice in Narcolepsy: Diagnostic Delay, Disease Burden, and Treatment Efficacy

Abstract: Study Objectives: Describe common symptoms, comorbidities, functional limitations, and treatment responsiveness among patients with narcolepsy. Investigate the effect of pediatric onset of narcolepsy symptoms on time to diagnosis of narcolepsy and presence of comorbid depression. Methods: Cross-sectional survey of 1,699 people in the United States with self-reported diagnosis of narcolepsy. We utilized mixed-methods data analyses to report study findings. Results: Most participants reported receiving a diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 30 publications
(34 reference statements)
1
72
0
Order By: Relevance
“…Excessive sleepiness (ES) and impaired daytime wakefulness are essential and somewhat independent symptoms of narcolepsy . These symptoms contribute to reductions in function, productivity, and quality of life, and an increased risk for motor vehicle accidents . Although ES and impaired wakefulness are present in all individuals with narcolepsy, 2 types of narcolepsy are recognized: type 1 and type 2, formerly known as narcolepsy with and without cataplexy, respectively.…”
mentioning
confidence: 99%
“…Excessive sleepiness (ES) and impaired daytime wakefulness are essential and somewhat independent symptoms of narcolepsy . These symptoms contribute to reductions in function, productivity, and quality of life, and an increased risk for motor vehicle accidents . Although ES and impaired wakefulness are present in all individuals with narcolepsy, 2 types of narcolepsy are recognized: type 1 and type 2, formerly known as narcolepsy with and without cataplexy, respectively.…”
mentioning
confidence: 99%
“…Some of the reported therapeutic challenges for the narcolepsy community included variable responsiveness and limited access to available treatment options, as well as intolerable drug side effects. 42 The Maski et al 43 report of the Unite Narcolepsy survey, administered in conjunction with the PFDDI meeting, indicated that 57.1% of people with narcolepsy experienced daytime sleepiness or fatigue three or more times per day in spite of treatment while only 3.9% reported no daytime sleepiness in response to treatment. The lack of perceived efficacy, as well as side effects, drug interactions, and high costs, likely contribute to inconsistent medication use.…”
Section: Treatment Landscape For Narcolepsymentioning
confidence: 99%
“…Alternatively, these features may be related to or even confused with the sense of cognitive impairments such as mental fog and difficulty thinking. Cognitive features, such as mental fogginess, have been found to be among the most significant symptoms affecting the daily life of patients with narcolepsy [ 19 ]. Hyperactivity seen in ADHD may, in fact, be a compensatory response for individuals who are under-aroused or sleepy [ 11 ].…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%